IMPLEMENTATION OF MINIMUM SERVICE STANDARDS IN HULAWA VILLAGE, PAGUYAMAN DISTRICT: PENERAPAN STANDAR PELAYANAN MINIMAL DI DESA HULAWA KECAMATAN PAGUYAMAN - RATNA OTOLUWA; Imam Mashudi; Syamsinah (Jurnal Ilmu Manajemen dan Bisnis, 2023)
Research objectives is For know application standard minimum service in Hulawa Village Paguyaman Regency Boalemo . The research method used is approach qualitative with type study descriptive . method data collection used in study This is observation , interview and documentation. Technique data analysis used is technique qualitative data analysis , with stages as proposed by Miles and Haberman is data reduction , data presentation and withdrawal conclusion / verification . Research results is application standard minimum service in Hulawa Village Not yet fully walk with ok . Good standard minimum service provision and distribution information sometimes found community _ or visited at home No is at place . Standard service provision of data and information administration population in Hulawa Village must adapt with renew document already _ There is with a new format . Application standard service gift letter information in Hulawa Village it turns out encountered in the manufacturing process letter information finished For signing letter sometimes Village head / Secretary of Village No be in place . Application standard minimal service simplification service in Hulawa Village rated own lack facilities and infrastructure supporters in make letter information or administration other . Application standard minimum form of service complaint public in implementation service found public No own letters completeness management administration at the Hulawa Village Office .